2014
DOI: 10.1007/s10646-014-1384-6
|View full text |Cite
|
Sign up to set email alerts
|

The molecular and physiological impact of bisphenol A in Sesamia nonagrioides (Lepidoptera: Noctuidae)

Abstract: In the present study we investigated the potential relative effects of bisphenol A (BPA) and RH-5992 (tebufenozide) on the development and metamorphosis of the corn stalk borer, Sesamia nonagrioides (Lepidoptera: Noctuidae). A number of morphological and molecular factors were examined in order to identify the toxic and the endocrine-relative action of these two chemicals. We observed that BPA, RH-5992 and the combination of BPA/RH-5992 caused a developmental delay by extending the transition period between la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Studies on lepidopteran corn stalk borer Sesamia nonagrioides revealed that BPA induces various developmental disorders through interfering efect in ecdysteroidal pathway [105] and over expression of heat-shock proteins [106]. Study on freshwater insect Chironomus riparius showed that adult emergence times were signiicantly delayed on moderate BPA exposure [107].…”
Section: Efects On Life History Traits and Developmental Eventsmentioning
confidence: 99%
“…Studies on lepidopteran corn stalk borer Sesamia nonagrioides revealed that BPA induces various developmental disorders through interfering efect in ecdysteroidal pathway [105] and over expression of heat-shock proteins [106]. Study on freshwater insect Chironomus riparius showed that adult emergence times were signiicantly delayed on moderate BPA exposure [107].…”
Section: Efects On Life History Traits and Developmental Eventsmentioning
confidence: 99%